2020
DOI: 10.21093/at.v6i1.2497
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influence Financial Sustainability Banking In Indonesia

Abstract: This research aims to determine the factors that affect the financial sustainability of conventional banks and sharia banks in Indonesia. Data obtained from the financial statements of conventional commercial banks and Islamic commercial banks have been published by the Financial Services Authority (OJK) for the period 2014 to 2018. The total population used in this study are all conventional and Sharia banks that publish their financial statements on the OJK. The research variables used include Financial Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…The probability value of the Z variable (profitability) is 0.00 < 0.05, and the coefficient of Z is positive, indicating that profitability has a positive impact on financial sustainability. This research aligns with studies conducted by Marheni (2022), Rianasari & Pangestuti (2016), Sholikah & Miranti (2020), and Sutikno & Aisyah (2022), stating that ROA has a positive and significant effect on financial sustainability. Consistent with Marheni's study (2022), if a company has high profitability, it will become more active in implementing financial sustainability because the implementation of financial sustainability also requires expenses.…”
Section: The Influence Of Profitability (Roa) On Financial Sustainabi...supporting
confidence: 91%
See 3 more Smart Citations
“…The probability value of the Z variable (profitability) is 0.00 < 0.05, and the coefficient of Z is positive, indicating that profitability has a positive impact on financial sustainability. This research aligns with studies conducted by Marheni (2022), Rianasari & Pangestuti (2016), Sholikah & Miranti (2020), and Sutikno & Aisyah (2022), stating that ROA has a positive and significant effect on financial sustainability. Consistent with Marheni's study (2022), if a company has high profitability, it will become more active in implementing financial sustainability because the implementation of financial sustainability also requires expenses.…”
Section: The Influence Of Profitability (Roa) On Financial Sustainabi...supporting
confidence: 91%
“…These findings are inconsistent with studies conducted by Dini ( 2021 2020), which suggest that NUC financing has a significant negative impact on ROA. Furthermore, these results do not align with research by Sholikah & Miranti (2020) and Sutikno & Aisyah (2022), which state that profitability (ROA) has a significant positive impact on financial sustainability. Therefore, it can be concluded that the profitability variable cannot mediate the influence of NUC financing on financial sustainability.…”
Section: The Indirect Influence Of Natural Uncertainty Contracts (Nuc...contrasting
confidence: 73%
See 2 more Smart Citations